2014
DOI: 10.1007/s00484-014-0881-x
|View full text |Cite
|
Sign up to set email alerts
|

Nut crop yield records show that budbreak-based chilling requirements may not reflect yield decline chill thresholds

Abstract: TitleNut crop yield records show that budbreak-based chilling requirements may not reflect yield decline chill thresholds Abstract Warming winters due to climate change may critically affect temperate tree species. Insufficiently cold winters are thought to result in fewer viable flower buds and the subsequent development of fewer fruits or nuts, decreasing the yield of an orchard or fecundity of a species. The best existing approximation for a threshold of sufficient cold accumulation, the "chilling requireme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
23
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 31 publications
0
23
0
1
Order By: Relevance
“…Despite research suggesting that declines in crop suitability due to climate change may not be as severe as shown in our results [45], it is worth noting that we examined changes in chill accumulation under a conservative, moderate warming scenario. Provided that some degree of reductions in suitability are anticipated for peach crops across the SEUS-as well as for other crops with similar chill requirements-adaptive measures may be warranted to maintain production.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Despite research suggesting that declines in crop suitability due to climate change may not be as severe as shown in our results [45], it is worth noting that we examined changes in chill accumulation under a conservative, moderate warming scenario. Provided that some degree of reductions in suitability are anticipated for peach crops across the SEUS-as well as for other crops with similar chill requirements-adaptive measures may be warranted to maintain production.…”
Section: Discussionmentioning
confidence: 64%
“…While this warming may offer range expansion for cold-intolerant crops, the related reduction in the winter chill accumulation in subtropical climates like the SEUS is projected to have negative impacts on warm-region fruit and nut crops, particularly those with moderate and high chill requirements [20,21]. However, the degree to which these declines may impact crop yield is unclear as uncertainties remain regarding the chill requirements that are physiologically needed for production, and the overall effect of marginal chill accumulation on crop yield and quality [44,45]. For example, while a common commercial peach cultivar grown in central Georgia has a stated chill requirement of 850 h, Georgia peach specialists have suggested that only 800 h are needed for a suitable crop [4].…”
Section: Discussionmentioning
confidence: 99%
“…To further complicate the logistics of harvesting and marketing the crop, the ability of the pistachio industry to estimate the size of the crop in advance is limited (Klein, 2016). The alternate-bearing nature of pistachio and years with what appears to be insufficient winter chilling complicate estimating annual crop production (Jackson et al, 2009;Pope et al, 2015). Basic physiological information on how annual yield is affected by winter Ta and Ta during the growing season is lacking (Pope et al, 2015).…”
mentioning
confidence: 99%
“…The alternate-bearing nature of pistachio and years with what appears to be insufficient winter chilling complicate estimating annual crop production (Jackson et al, 2009;Pope et al, 2015). Basic physiological information on how annual yield is affected by winter Ta and Ta during the growing season is lacking (Pope et al, 2015). Timely advance knowledge of the magnitude of the yield of the next pistachio harvest would be beneficial for the pistachio industry for efficient allocation of harvest and postharvest resources, such as personnel, harvesting machinery, trucks, processing facility capacity, crop storage facilities, and for making marketing decisions.…”
mentioning
confidence: 99%
See 1 more Smart Citation